Associations between nutritional status and jumping performance in pre-school children - Sanja Ljubičić; Vilko Petrić; Ljubomir Antekolović (PLoS ONE, 2025)
Although it has been confirmed that overweight and obesity may have negative impact on jumping performance in school-aged children and adolescents, little evidence has been provided for pre-school children. The findings have provided inconclusive results, but mostly that overweight and obese pre-school children do not have an impaired jumping performance, in comparison to their normal weight peers. Therefore, the main purpose of the study was to examine the differences between normal weight and overweight/obese pre-school children in jumping performance outcomes and their correlations with anthropometric indices. Four-hundred and eleven pre-school children with the mean (SD) age = 4.9 (1.1) years, height = 111.2 (9.3) cm, weight = 20.0 (4.2) kg, 53.5% girls were recruited from 34 kindergartens in four major cities. Anthropometric indices included body mass index (BMI), waist-to-hip ratio (WHR), and waist-to-height ratio (WHtR). Normal weight, overweight and obesity were classified according to international norms. Jumping performance was evaluated by the countermovement jump (CMJ) without and with arm swing with Optojump system. In general, pre-school children with overweight and obesity exhibited poorer performance in vertical jumping; they had shorter flight time and flight height, lower power relative to body mass and lower relative strength index (RSI), compared to normal weight children. The strongest correlations were observed between WHtR and jumping outcomes, where higher WHtR values led to shorter flight time and flight height, and lower power relative to body mass in both boys and girls. This study adds new information related to nutritional status and jumping performance in pre-school children. Thus, overweight and obesity need to be considered, when monitoring vertical jumping performance.